Pengaruh Aktivitas Fisik Senam Aerobik Low Impact Terhadap Penurunan Kadar Gula Darah Pada Penderita Diabetes Melitus Tipe 2: The Effect of Low-Impact Aerobic Exercise on Blood Glucose Reduction in Patients with Type 2 Diabetes Mellitus - Syafitri, Mutiara; Utami, Wiwik; Rahmawati, Rahmawati (Chakra Brahmanda Lentera Institute, 2026)
Type 2 Diabetes Mellitus (T2DM) is a chronic metabolic condition characterized by insulin resistance and impaired glucose metabolism, leading to elevated blood sugar levels. Effective blood glucose management is essential to prevent serious complications such as cardiovascular disease, renal failure, and neuropathy. This study aimed to investigate the impact of low-impact aerobic exercise on blood glucose levels among T2DM patients. This study employed a quasi-experimental design with a pre-test and post-test approach. A total of 74 participants were divided into two groups: an intervention group (n=37) that underwent a two-week low-impact aerobic exercise program, and a control group (n=37) that received no intervention. Respondent demographic characteristics included age, gender, education level, and occupation. Blood glucose levels were measured using a standardized digital glucometer. Data were analyzed using paired t-tests and independent t-tests with a significance level of p < 0.05. The results showed a significant decrease in mean blood glucose levels within the intervention group, dropping from 266.27 mg/dL to 173.14 mg/dL (p=0.001). Conversely, the control group showed no significant difference, with blood glucose levels changing from 256.83 mg/dL to 259.22 mg/dL. The independent t-test confirmed a significant difference between the intervention and control groups following the intervention (p=0.001). In conclusion, low-impact aerobic exercise is effective in reducing blood glucose levels in T2DM patients. Based on these findings, low-intensity physical activity is recommended as a safe and effective non-pharmacological management strategy for diabetes patients to maintain routine glycemic control.